Clinical validation and application of targeted long-range polymerase chain reaction and long-read sequencing–based analysis for hemophilia: experience from a hemophilia treatment center in China - Shi, Meizhen; Ma, Yunting; Peng, Xianwei; Zhou, Xu; Cheng, Zifeng; Xie, Bobo; Wei, Xianda; Gui, Chunrong; Mao, Aiping; Lin, Wenting; Luo, Jiefeng; Lai, Yinghui; et al. (Journal of thrombosis and haemostasis, 2024)
Targeted long-read sequencing (LRS) is expected to comprehensively analyze diverse complex variants in hemophilia A (HA) and hemophilia B (HB) caused by the F8 and F9 genes, respectively. However, its clinical applicability still requires extensive validation. To evaluate the clinical applicability of targeted LRS-based analysis compared with routine polymerase chain reaction (PCR)–based methods. Gene variants of retrieved subjects were retrospectively and prospectively analyzed. Whole-genome sequencing was performed to further analyze undiagnosed cases. Breakpoints of novel genomic rearrangements were mapped and validated using long-distance PCR and long-range PCR combined with sequencing. In total, 122 subjects were retrieved. In retrospective analysis of the 90 HA cases, HA-LRS assay showed consistent results in 84 cases compared with routine methods and characterized 6 large deletions with their exact breakpoints confirmed by further validation in 6 cases (routine methods only presented failure in amplifying the involved exons). In prospective analysis of the 21 HA subjects, 20 variants of F8 were identified in 20 cases. For the remaining HA patient, no duplication/deletion or single-nucleotide variant (SNV)/insertion and deletion (InDel) was found, but a potential recombination involving exons 14 and 21 of F8 was observed by LRS. Whole-genome sequencing analysis and further verification defined a 30 478 base pairs (bp) tandem repeat involving exons 14 to 21 of F8. Among the 11 HB patients, HB-LRS analysis detected 11 SNVs/InDels in F9, consistent with routine methods. Targeted LRS-based analysis was efficient and comprehensive in identifying SNVs/InDels and genomic rearrangements of hemophilia genes, especially when we first expanded the panel to include F9. However, further investigation for complex gross rearrangement is still essential.